Pengaruh Brand Ambassador Lee Min-Ho Terhadap Brand Awareness E-Commerce Lazada (Survei pada Pengikut @lazada_id) - Tabina Chairani Faridi; agustrijanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
The phenomenon of using actors and bands from South Korea as brand ambassadors is often busy being applied by many companies, one of which is a company in the e-commerce field, including the e-commerce company Lazada which uses Lee Min-Ho's brand ambassador. One of the goals in using a brand ambassador is to build brand awareness. So from the phenomenon that occurs, researchers want to find out the influence and how much influence Lee Min-Ho's brand ambassador has on Lazada's e-commerce brand awareness. The data was taken through distributing questionnaires to Instagram followers @lazada_id and the data was processed using Pearson Product Moment correlation analysis and simple linear regression. The results of this study are Lee Min-Ho's brand ambassador has a positive influence of 0.590 on Lazada's e-commerce brand awareness. In addition, the big influence given by brand ambassador Lee Min-Ho is 34.8% on Lazada's e-commerce brand awareness.